ETHNIC TENSIONS IN CHINA: XINJIANG CONFLICT IN CONSTRUCTIVISM PERSPECTIVE - Melpayanty Sinaga; Yusril y (Polteknik Imigrasi, 2021)
The People's Republic of China is one of the multi-ethnic countries in this world that is facing a number of prominent ethnic issues, including the Xinjiang Conflict which has received international attention in recent years. In the China's western autonomous region, ethnic tensions exist between the Han majority and the Uighur minority. This research is using a qualitative-descriptive method by relying on library studies from available secondary sources, this paper will try to explain the tension between the Uighurs and Hans ethnic groups through a constructivism perspective. In constructivism perspective, identity is one of the main ideas that shape the pattern of interaction between actors. It was found that the construction of Uighur and Han ethnic identities contributed to the creation of this ethnic tension, which is also related to how the conception of China's national identity is constructed.